МОНГОЛ ДАХЬ ПАРЛАМЕНТЫН СОНГУУЛИЙН ҮЙЛ ЯВЦ, ТУЛГАМДСАН АСУУДЛУУД - Д.Оюунчимэг (Politology, 2023)
Impact of election system into political party system, Parliament, Government, electoral psychology and political stability has been revised in the article. Ascertainment of issues raised around the actualization of Parliamentary election system has crucial importance of investigation.